2017
DOI: 10.1186/s12885-017-3852-x
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser therapy (Photobiomodulation therapy) for breast cancer-related lymphedema: a systematic review

Abstract: BackgroundBreast cancer related lymphedema (BCRL) is a prevalent complication secondary to cancer treatments which significantly impacts the physical and psychological health of breast cancer survivors. Previous research shows increasing use of low level laser therapy (LLLT), now commonly referred to as photobiomodulation (PBM) therapy, for BCRL. This systematic review evaluated the effectiveness of LLLT (PBM) in the management of BCRL.MethodsClinical trials were searched in PubMed, AMED, Web of Science, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 52 publications
1
57
0
3
Order By: Relevance
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
“…The review indicated strong evidence for limb circumference/volume reduction over sham treatment, moderate evidence for short-term pain relief over sham laser treatment, and limited evidence for limb swelling over no treatment. 26 Mahram and Rajabi 25 reported that LLLT in a patient with LEL had reduced edema, but it did not result in a reduction in extremity volume. In our study, we found a significant decrease in both edema and extremity volume with LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was applied in the supine position with leg abduction and external rotation. 26 The LLLT was administered every day for the first 4 weeks and then 2 days a week for 8 weeks.…”
Section: Interventionsmentioning
confidence: 99%
“…There is no cure for lymphedema; however, there are several options for treatment aiming to control symptoms and reduce recurrent rate, using complete decongestive therapy (CDT), and exercise therapy [8,9]. Additional management options include pneumatic pumps [10], low-level laser therapy [11], and kinesiotaping [12].…”
Section: Introductionmentioning
confidence: 99%